The Development of Algorithm For Charging Material Cost Reduction In Terms of Manganese Sinter Production (Modern Problems of Metallurgy, 2019)
Manganese ores in Ukraine are beneficiated, thus such concentrates come in small fractions. Before the melting process such concentrates undergo sintering.The research study presents the results of simplex algorithm application in terms of developing mathematical model for charging material cost reduction while sintering manganese agglomerates (АМНВ-1 and АМНВ-2) with defined level of manganese out of various manganese raw materials and while processing their own wastes that still contain manganese. Comparative analysis of the quality of initial manganese raw material used for sintering process that was conducted while following the module parameter (i.e. the relationship between the contents of the element xi (P, Mn, Fe, SiO2) and manganese) reveal that concentrates from the deposits in Nikopol have less module of iron compared to ores imported, for instance, from SAR, Brazil, Australia, etc. While solving the mentioned above problem, the following statement should be taken into consideration: ЕН.П ≤ Е ≤ ЕВ.П, where E - states for the element (manganese) along with its lower (ЕН.П) and upper (ЕВ.П) limits of content in various sinter grades, mass %.The addition of low-grade concentrate in terms of АМНВ-1 agglomerate sintering may result in increased consumption of high-grade manganese concentrate. Moreover, the addition of high-grade manganese concentrate in terms of АМНВ-2 agglomerate sintering (respecting the limits of manganese, as it should be) may result in diluting it either with lower-grade manganese concentrate or its own oxide wastes. The amount of added wastes is limited due to its availability and reasonability from engineering point of view.The important criteria for defining the amount of agglomerate mass based on initial indices of charging material are the coefficient of solid sinter output from each i-row component of this charging material and the percentage of this solid sinter in agglomerate mass.The developed algorithm suggests acceptable solutions while changing the percentage of charging material components in agglomerate charging material with its chemical content, solid waste output from each charging material component. Mathematical model helps develop software system that makes integrated efficient and strategic estimation possible. This implies charging material cost reduction while taking into account quite large range of aspects of acceptable and adjustable solutions in certain manufacturing contexts.The described results can be used for software system development in order to make acceptable and adjustable solutions regarding the management of sintering process in specified manufacturing contexts of JSC «Nikopol Ferroalloy Plant».
Keywords: manganese; extraction; charge; waste; agglomerate; solid residue; mathematical model; algorithm; cost optimization